Beneficial vascular risk profile is associated with amyotrophic lateral sclerosis. Issue 6 (6th April 2011) - Sutedja, N A; van der Schouw, Y T; Fischer, K; Sizoo, E M; Huisman, M H B; Veldink, J H; Van den Berg, L H
Abstract : Objectives: Reports of increased amyotrophic lateral sclerosis (ALS) with hyperlipidaemia and elevated plasma homocysteine levels as well as cigarette-smoking and polymorphisms in angiogenic genes suggest a role for altered vascular homeostasis in ALS pathogenesis. The authors assessed the association between vascular risk factors and ALS. Methods: Traditional cardiovascular risk factors (smoking, hypertension, hypercholesterolaemia, diabetes and body mass index (BMI)) and cardiovascular disease prior to ALS onset established by a questionnaire were compared in 334 patients and 538 age- and sex-matched controls. Biochemical assessments (total cholesterol (TC), low-density lipoprotein (LDL), high-density lipoprotein (HDL), hs-CRP, and homocysteine) at diagnosis were measured in blood samples of 303 patients with ALS and compared with prospectively collected data from 2100 population-based controls. Results: Patients with ALS used cholesterol-lowering agents less frequently (OR=0.6, p=0.008) and had a lower BMI (OR=0.9, p=0.001), a lower LDL/HDL ratio (women: OR=0.5, p<0.001; men: OR=0.4, p<0.001) and lower homocysteine levels (women: OR=0.9, p=0.02; men: OR=0.9, p<0.001). The mean LDL and TC levels were significantly lower among patients with a lower functional vital capacity percentage of predicted (FVC). In the univariate analysis, a higher LDL/HDL ratio correlated with increased survival (HR=0.9, p=0.04); after adjusting for the confounders age, site and FVC, no difference was observed. Conclusions: Vascular risk factors, measured clinically and biochemically, were not associated with increased ALS. Instead, patients reported less use of cholesterol-lowering medication and had a lower premorbid BMI and favourable lipid profile—all findings consistent with the hypothesis that a higher metabolic rate plays a role in ALS.